Penyerapan Emisi CO2 Dari Kendaraan Bermotor Melalui Teknologi Vegetasi di Ruang Milik Jalan - Hidayat, Edwin (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2013)
Motor vehicles growing rapidly each year in Indonesia, beside have positive impact, on the other hand it’s also brings negative impact, one of them is resulting Greenhousegas, especially CO2 emission from fosil fuel burning. Where as, the growth of motor vehicle emissions give contribution for global warming and contribute to the climate change. One way to overcome the problem of motor vehicle emission is vegetation technology for CO2 sequetration. Thus, for indentifiying how much the carbon stock and the value of CO2 sequestration from motor vehicles emissions by tree, we conduct case study in the AH. Nasution road – Bandung City, the methodology is using emission factor approachment and biomass method. The result shows that CO2 from traffic emissions are averagely 97.914 kgCO2/Day and the CO2 seguestration from the tree until the survey conducted are 1.506.662 kg. Thus, we can assume that vegetation technology is not significant enough for reducing the CO2 emission. In the future to decrease the motor vehicle emissions, we need the species of plants which have huge sequestration, on the other hand also to be recommended to developed mass rapid transportation or converstion the fuel to non fosil fuel.